Antimicrobial activity of commercial calcium phosphate based materials functionalized with vanillin. (November 2018) - Polo, Lorena; Díaz de Greñu, Borja; Della Bella, Elena; Pagani, Stefania; Torricelli, Paola; Vivancos, José Luis; Ruiz-Rico, María; Barat, José M.; Aznar, Elena; Martínez-Máñez, Ramón; Fini, Milena; Sancenón, Félix
Graphical abstract: Abstract: Infections represent one of the most frequent causes of arthroplasty revision. Thus, design of new antimicrobial scaffolds to reduce implant rejections, bone infections and associated medical costs is highly desired. In recent years, essential oil components (EOCs) have merged as compounds with significant antimicrobial activity that can be attached to specific surfaces to enhance and prolong their antimicrobial effect. Herein calcium phosphate CaP regenerative materials have been coated with a vanillin derivative to combine its original bone regeneration properties with antimicrobial action of EOCs. Materials in form of microparticles and blocks were prepared and fully characterized. Clonogenic viability tests demonstrated that low concentrations of material (10 mg·mL −1 ) resulted effective to kill 100% of E. coli DH5α bacteria. Additionally, vanillin containing scaffolds did not display any toxic effect over cells, yet they preserve the ability to express alkaline phosphatase ( ALPL), collagen type 1, chain α1 ( COL1A1) and bone gamma-carboxyglutamic acid-containing protein or osteocalcin ( BGLAP), which are genes typically expressed by osteoblasts . These results demonstrate that commercially available scaffolds can be functionalized with EOCs, achieving antimicrobial activity and open up a new approach for the treatment and prevention of infection. Statement of significance: During the last years, the interest in bone regenerative materials with antibiotic properties has increased, since prosthesis infection is one of the most usual complications in implant surgery. In this work, we report a hybrid system composed by a calcium phosphate material (powders and scaffolds) functionalized with the derivative of an essential oil component (EOC). Our purpose was to provide the calcium phosphate material with antimicrobial activity without harming its bone regenerative capability. The obtained results were encouraging, which opens up the possibility of developing new modified materials for the prevention and treatment of bone infection.